Pengaruh Literasi Keuangan dan Kemudahan Bertransaksi Terhadap Minat Generasi Millenial Dalam Menggunakan Dompet Digital (ShopeePay) - Erin Soleha; Zulfa Zakiatul Hidayah (ARBITRASE: Journal of Economics and Accounting, 2022)
Along with the development of increasingly advanced times, society must be able to accept and adapt quickly. One of them is the presence of financial technology, in everyday life technological developments also occur in the financial sector. This study aims to determine the influence of financial literacy and ease of transactions on the millennial generation's interest in using digital wallets (Shopee Pay). The population in this study is the millennial generation community in West Java province. The sampling technique uses accidental sampling. Data analysis using Smart PLS softwere. The results showed that financial literacy had a significant positive effect on interest in use by 79.84% and ease of transaction had a significant positive effect on interest in use by 60.26%.